Inhibiting autophagy reduces retinal degeneration caused by protein misfolding. Issue 7 (3rd July 2018) - Yao, Jingyu; Qiu, Yaoyan; Frontera, Eric; Jia, Lin; Khan, Naheed W.; Klionsky, Daniel J.; Ferguson, Thomas A.; Thompson, Debra A.; Zacks, David N.
ABSTRACT: Mutations in the genes necessary for the structure and function of vertebrate photoreceptor cells are associated with multiple forms of inherited retinal degeneration. Mutations in the gene encoding RHO (rhodopsin) are a common cause of autosomal dominant retinitis pigmentosa (adRP), with the Pro23His variant of RHO resulting in a misfolded protein that activates endoplasmic reticulum stress and the unfolded protein response. Stimulating macroautophagy/autophagy has been proposed as a strategy for clearing misfolded RHO and reducing photoreceptor death. We found that retinas from mice heterozygous for the gene encoding the RHO P23H variant (hereafter called P23H) exhibited elevated levels of autophagy flux, and that pharmacological stimulation of autophagy accelerated retinal degeneration. In contrast, reducing autophagy flux pharmacologically or by rod-specific deletion of the autophagy-activating gene Atg5, improved photoreceptor structure and function. Furthermore, proteasome levels and activity were reduced in the P23H retina, and increased when Atg5 was deleted. Our findings suggest that autophagy contributes to photoreceptor cell death in P23H mice, and that decreasing autophagy shifts the degradation of misfolded RHO protein to the proteasome and is protective. These observations suggest that modulating the flux of misfolded proteins from autophagy to the proteasome may represent an important therapeutic strategy for reducing proteotoxicity in adRP and other diseases caused by protein folding defects.